Numerical analysis of the construction of Odelouca Dam using a Subloading Surface Soil Model - Brito, A. (2014)
Odelouca dam is an embankment dam, with 76 m height, recently constructed in the south of Portugal. It is zoned with a core consisting of colluvial and residual schist soil, and with soil-rockfill mixtures making up the shells (weathered schist with a significant fraction of coarse sized particles). This paper presents a numerical analysis of Odelouca dam construction. In this analysis the explicit finite difference program FLAC is used. An unconventional elastoplastic soil model, a Subloading Surface type model, implemented into the program, is used to model the embankment materials. The main results are compared with those obtained with the Modified Cam Clay Model. The model’s constants and internal variables initial values are determined from a comprehensive testing programme carried out in the Civil Engineering National Laboratory (LNEC) for the hydraulic and mechanical characterization of the materials used and a Subloading Surface type model with plastic anisotropy is used to model its behaviour. Computational results are then compared to the ones obtained from the dam’s monitoring system during the construction stage.